2016
DOI: 10.1074/jbc.m116.739425
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Divergence in Nucleotide Excision Repair Lesion Recognition

Abstract: Nucleotide excision repair is an important and highly conserved DNA repair mechanism with an exceptionally large range of chemically and structurally unrelated targets. Lesion verification is believed to be achieved by the helicases UvrB and XPD in the prokaryotic and eukaryotic processes, respectively. Using single molecule atomic force microscopy analyses, we demonstrate that UvrB and XPD are able to load onto DNA and pursue lesion verification in the absence of the initial lesion detection proteins. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…Numerous complexes have been proposed to form during NER in prokaryotes; however, their dynamics and specific roles remain uncertain. Single-molecule and ensemble approaches have been used previously to reveal the existence of UvrAB ( 4 , 6 , 9 , 11 ) and UvrBC ( 19 , 20 , 22–24 ) complexes, which likely represent the most populated forms in vivo . The UvrAB complex is well established in damage search; however a role for the UvrBC complex in a process other than DNA incision is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous complexes have been proposed to form during NER in prokaryotes; however, their dynamics and specific roles remain uncertain. Single-molecule and ensemble approaches have been used previously to reveal the existence of UvrAB ( 4 , 6 , 9 , 11 ) and UvrBC ( 19 , 20 , 22–24 ) complexes, which likely represent the most populated forms in vivo . The UvrAB complex is well established in damage search; however a role for the UvrBC complex in a process other than DNA incision is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations suggested, in agreement with bulk studies ( 9 , 13 ), that UvrA and UvrB formed a UvrA 2 B 2 complex. In addition, UvrB and UvrC were also observed to form a complex independently of UvrA ( 19 , 20 ). This intriguing complex has been previously identified during bulk studies ( 21 , 22 ), but has shown no apparent repair efficiency on dsDNA in vitro ( 20 , 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been postulated that certain helicases (e.g., XPB, XPD) play a role in the recognition or verification of bulky DNA damage [2631]. It is less certain but plausible that other helicases (e.g., RecQ members) may sense DNA damage as a component of the replication stress response [32].…”
Section: Single Oxidative Base Lesions Differentially Affect Unwindinmentioning
confidence: 99%
“…To maintain the balance required for survival and diversity, evolution has equipped all life forms with mechanisms to either eliminate or tolerate DNA damage. Basic strategies for DNA repair include removing individual damaged nucleotides via the base excision repair (BER) mechanism [4] or by excising longer sections containing helix-distorting bulky lesions through the nucleotide excision repair (NER) mechanism[5]. …”
Section: Introductionmentioning
confidence: 99%